2015
DOI: 10.1007/s10853-014-8812-0
|View full text |Cite
|
Sign up to set email alerts
|

In situ analysis of the influence of twinning on the strain hardening rate and fracture mechanism in AZ31B magnesium alloy

Abstract: The influence of twinning on the strain hardening rate and fracture mechanism in AZ31B magnesium alloy was studied in this work by in situ microstructural analysis during tensile testing in a chamber of scanning electron microscope. Three types of samples used in this study were obtained by (1) extrusion (as-supplied), (2) I-ECAP and (3) I-ECAP followed by side upsetting. Microstructures, textures and mechanical properties were examined after each processing step. An analytical equation was used to describe fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Despite I-ECAPed texture indicating importance of this kind of deformation, it was shown that microstructure of the annealed sample was severely twinned at true strain 0.15. It is especially interesting as twinning is usually expected to decrease ductility [31][32][33] while in this work it was revealed in the sample, which exhibited extraordinary elongation along tensile direction. EBSD analysis of the deformed structure (Fig.…”
Section: Ductility Enhancement By Heat Treatmentmentioning
confidence: 70%
“…Despite I-ECAPed texture indicating importance of this kind of deformation, it was shown that microstructure of the annealed sample was severely twinned at true strain 0.15. It is especially interesting as twinning is usually expected to decrease ductility [31][32][33] while in this work it was revealed in the sample, which exhibited extraordinary elongation along tensile direction. EBSD analysis of the deformed structure (Fig.…”
Section: Ductility Enhancement By Heat Treatmentmentioning
confidence: 70%
“…In this study, we discussed over the reasonability of definite element analysis of steel reinforced concrete structure [23]. It can be known from the actual measurement of deformation that, deformation rate of steel reinforced concrete (C60, C50) column in low floor became higher than the simulated value in the late period; and the vertical deformation of steel reinforced concrete (C50, C60) column was smaller than that of steel reinforced concrete (C40) column [24]. During construction, deformation of structural component and accumulation of stress are different as construction order and procedures of exerting construction load are different.…”
Section: Resultsmentioning
confidence: 99%
“…Mg-Li alloy is one of the lightest structural metallic materials, which shows great potential in transportation systems and electric equipments due to the high specific strength and good formability at ambient temperature. 1,2 Furthermore, The addition of Li to magnesium alloy can not only reduce its density but also markedly improve the formability by changing the crystal structure from hexagonal close packed to body centred cubic (BCC) when the amount of Li exceeds 11 wt-%. 3 The b-phase Mg-Li alloy has lower density and better formability than other a-phase or (a þ b)-phase alloys.…”
Section: Introductionmentioning
confidence: 99%